ANALYSIS OF LEAD WASTE ABSORPTION (Pb) WITH ACTIVATED CHARCOAL ADSORBENT FROM PALM SHELL - SRI SURYANINGSIH (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Some industries, especially the textile industry in general, use textile dyes containing lead heavy metals (Pb). Lead is a metal that is neurotoxin (toxic to the nervous system) and is accumulative because of its stable nature and has a long half-life, and it can be harmful to the environment and needs to be filtered using adsorbent. This study aims to find out the absorption of activated charcoal palm shell as adsorbent to eliminate lead waste. The method used by varying the concentration of and KOH activator solutions with concentrations of 20%, 30% and 40% respectively. Batch method is done to mix activated charcoal into Pb solution with variation of contact time of 30 minutes, 60 minutes, 90 minutes. SEM (Scanning Electron Microscope) and AAS ((Atomic Absorption Spectrophotometer) tests are conducted to find out the pore area and absorption. SEM test results showed that the best activator is KOH with a concentration of 40% compared to activators with the largest average pore area of 31.755 micrometer. AAS test results obtained the most absorption of 98.59% by activated charcoal KOH 30% at a contact time of 60 minutes.Keywords: adsorption, activators, palm shells, Pb acetate